Marketing Strategy and Islamic Business Ethics in Promoting Mudharabah Deposits at Bank Muamalat Sukaramai - Nurul Feni Saputri; Isra Hayati (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
This study explores the marketing strategy and application of Islamic business ethics in promoting mudharabah deposit products at Bank Muamalat KCP Sukaramai, Medan. The research aims to analyze how marketing strategies are implemented at the branch level and identify key challenges in attracting public interest to sharia-compliant investment products. A qualitative descriptive approach was used, employing case study methods through interviews, observation, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, covering data reduction, display, and conclusion drawing. The findings reveal that Bank Muamalat Sukaramai applies a marketing mix strategy consisting of product development, profit-sharing–based pricing, personal and digital promotion, and local community engagement. Ethical Islamic values such as honesty, transparency, and fairness are consistently upheld throughout the marketing process. The bank also integrates educational efforts to increase public understanding of mudharabah principles through seminars, profit-sharing simulations, and social media content. However, several challenges remain, including low public literacy on sharia finance, tight competition with conventional banks, shifting customer preferences toward digital platforms, and regulatory constraints. This study contributes to the literature on Islamic banking marketing by highlighting practical, ethical-based strategies that are adaptive to local branch contexts. The study offers insights for other Islamic financial institutions seeking to enhance the appeal of profit-sharing deposit products and foster consumer trust in line with Islamic principles.Keywords: Marketing Strategy; Mudharabah Deposit; Islamic Business Ethics; Sharia Banking; Marketing Mix.